HOW PERCEPTIONS OF COST, ACCESS, AND QUALITY DRIVE OUTPATIENT REVISIT INTEREST - Gaby Priscillia Putri; Mugi Wahidin; Anggun Nabila; Susi Shorayasari; Arif Rachman (Journal of Innovation Research and Knowledge, 2026)
Abstract: This research was motivated by a decrease in interest in revisiting patients at RSGM X, Jakarta, from 40.5% (2020) to 16.2% (2024).The purpose of the study was to analyze the relationship between cost perception, access, and service quality with outpatient revisit interest.The research method used a cross-sectional design of 63 patients by 2025 with quota sampling technique. Bivariate analysis used Chi-Square and Prevalence Ratio (PR) tests. The results showed that 57.1% of patients had low interest in repeat visits. The majority of respondents perceived high costs (74.6%), unaffordable access (68.3%), but good quality (61.9%). There was a significant relationship between cost perception (PR=5,787), access (PR=3,721), and quality (PR=2,875) and interest in repeat visits (p=0,000). Cost is the dominant factor with a risk of 5.8 times, followed by access and quality. There is a significant relationship between these three factors and interest in repeat visits. Priority recommendations are to improve access through integrated digital systems and flexible tariff schemes, as well as strengthen service quality through continuous surveys and empathic communication training.